A Review on Cold Start of Proton Exchange Membrane Fuel Cells - Zhongmin Wan; Huawei Chang; Shuiming Shu; Yongxiang Wang; Haolin Tang (Energies, 2014)
Successful and rapid startup of proton exchange membrane fuel cells (PEMFCs) at subfreezing temperatures (also called cold start) is of great importance for their commercialization in automotive and portable devices. In order to maintain good proton conductivity, the water content in the membrane must be kept at a certain level to ensure that the membrane remains fully hydrated. However, the water in the pores of the catalyst layer (CL), gas diffusion layer (GDL) and the membrane may freeze once the cell temperature decreases below the freezing point (Tf). Thus, methods which could enable the fuel cell startup without or with slight performance degradation at subfreezing temperature need to be studied. This paper presents an extensive review on cold start of PEMFCs, including the state and phase changes of water in PEMFCs, impacts of water freezing on PEMFCs, numerical and experimental studies on PEMFCs, and cold start strategies. The impacts on each component of the fuel cell are discussed in detail. Related numerical and experimental work is also discussed. It should be mentioned that the cold start strategies, especially the enumerated patents, are of great reference value on the practical cold start process.